Oblatopyrochroa bellula, an enigmatic new genus and species of Pyrochroinae (Coleoptera, Pyrochroidae) from Xizang, China - Qi Gao; Daniel K. Young; Zhao Pan (ZooKeys, 2024)
Oblatopyrochroa bellula, a new genus and species of Pyrochroinae Latreille, 1807 from Xizang, China, is described and illustrated. The antennae, cranial apparatus, and genitalia of the new genus form a truly unique set of characters not observed in any other pyrochroid genus. The taxonomic position and phylogenetic relationships of Oblatopyrochroa gen. nov. are also discussed but appear difficult to resolve.